ANALISIS KONSEKUENSI KEBAKARAN DAN LEDAKAN PEMODELAN ALOHA PADA POM BENSIN MINI X DI DEPOK TAHUN 2020 - Della Rosa Ningtias (2021)
The National Fire Protection Association recorded an average of 4.150 fires at gasoline stations per year from 2014-2018. Tugu Sub-District, Cimanggis District, is a fire prone area. One of the causes of fire was flammable materials. Mini gas station was a business that sells fuel oil. Mini gas station had fire and explosion risk that cause fatality, health problems, socio-economic losses, and environmental pollution. Fire and explosion would have an impact to the owner, consumers, and communities around the mini gas station. The purpose of this research was to analyze the consequences of fire and explosion at the "Mini Gas Station X" Depok in 2020. This research was a descriptive quantitative study using ALOHA software to predict the threat zone. The results showed the hazardous zone from the storage tank location for a fire pool was less than 10 meters away, BLEVE/fireball was 69 meters away, gas dispersion was less than 10 meters away, and no LOC value was exceeded for VCE. BLEVE/ fireball case was the worst scenario that can cause thermal radiation effects up to 152 meters from the storage tank location. A safe zone of more than 152 meters estimated in any direction can be used to plan evacuation routes and determine meeting points.